Together with my playmates: Preschoolers' peer relationships and interactions in small group settings - Wang Yili; Kajamies Anu; Hurme Tarja-Riitta; Palonen Tuire (Elsevier Ltd, 2022)
Researchers and professionals in the early childhood education context have expressed concern over children's social and emotional behaviours and peer relationships. The current study aimed to investigate how children's interactions in small groups are associated with their peer relationships. Another aim was to learn how children's peer interactions vary at the individual level. The study's participants were 16 five-to-six-year-old full-time kindergarteners. Social network analysis was conducted, based on sociometric nominations, to test the degree centrality of all 16 children's peer acceptance, preference and likability. Video-recorded interactions among all participants were analysed to calculate the children's frequency of prosocial and problem behaviours. Four children's interactions were analysed in more detail. Our results showed a positive correlation between children's peer preferences and their problem behaviours. Furthermore, we observed a positive correlation between children's mutual ties and their prosocial and problem behaviours. We found no linear developmental trend from individual-level interactions. Our results indicate that situational environments relate to children's peer relationships and interaction dynamics. Kindergarten teachers can use this study's results to consider various activities that would encourage children's active interactions with various peers from children's standpoints, rather than adults' perspective.